1999
DOI: 10.1002/(sici)1096-9888(199906)34:6<661::aid-jms818>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mass spectrometric analyses of Photofrin oligomers by fast atom bombardment mass spectrometry, UV and IR matrix-assisted laser desorption/ionization mass spectrometry, electrospray ionization mass spectrometry and laser desorption/jet-cooling photoionization mass spectrometry

Abstract: Photofrin (porfimer sodium) is a porphyrin derivative used in the treatment of a variety of cancers by photodynamic therapy. This oligomer complex and a variety of porphyrin monomers, dimers and trimers were analyzed with five different mass spectral ionization techniques: fast atom bombardment, UV and IR matrix-assisted laser desorption/ionization, electrospray ionization, and laser desorption/jet-cooling photoionization. All five approaches resulted in very similar oligomer distributions with an average olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 0 publications
0
16
0
6
Order By: Relevance
“…Among the many studies of MALDI mechanisms are a number that exhibit remarkably similar mass spectra for many wavelengths28, 29 and for both nanosecond and femtosecond pulse durations 19. In fact, Siegal et al have demonstrated that mass spectra of a given species seem to be independent not only of laser wavelength but even ionization techniques 15. These observations have sometimes been interpreted as evidence for a single MALDI mechanism operative at all wavelength regimes and laser pulse durations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many studies of MALDI mechanisms are a number that exhibit remarkably similar mass spectra for many wavelengths28, 29 and for both nanosecond and femtosecond pulse durations 19. In fact, Siegal et al have demonstrated that mass spectra of a given species seem to be independent not only of laser wavelength but even ionization techniques 15. These observations have sometimes been interpreted as evidence for a single MALDI mechanism operative at all wavelength regimes and laser pulse durations.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the details of the MALDI process are still actively debated, MALDI is widely used for the mass analysis of biomolecules, carbohydrates,10 polymers11 and hazardous waste components12, 13 and new developments, such as zeptomole sampling,14 continue to be driven empirically. However, the complications resulting from the use of different wavelengths,15–18 laser pulse durations,17, 19–21 matrix preparations,22–25 and ion extraction parameters26, 27 have made it difficult to develop mechanistic models that comprehend the great variety of experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…Este modo de ionização é versátil porque permite a ionização de compostos polares e pouco voláteis (Gaskell, 1997). O padrão utilizado foi a hematoporfirina IX já que este composto é o reagente de partida da síntese do Photogem, além de ser um dos constituintes (Mironov, 1990;Dougherty, 1987b;Kessel, 1985b) (Siegel, 1999).…”
Section: Espectrometria De Massaunclassified
“…O sinal com m/z em 1725Da é pouco intenso e poderia estar relacionado ao trímero (Siegel, 1999) encontrado no derivado de hematoporfirina.…”
Section: Espectrometria De Massaunclassified
See 1 more Smart Citation